«Improvement of the informational and methodological competence of students of pedagogical higher educational institutions by means of information and communication technologies - Drokina, A. (Problems of Engineer-Pedagogical Education, 2018)
This article is devoted to the problems of training of students of pedagogical higher educational institution in the conditions of informatization of education. It is found that the informational and methodological competence is one of the most important components of professional competence of the teacher, which increases the intellectual capacity and competitiveness. During our study, we revealed that the formation of the informational and methodical competence of future teachers should be designed as an open complex dynamic system, which integrates a special, informational, psychological-pedagogical and subject-didactic training of future specialists. Based on the analysis of the potential and didactic possibilities of the information and communication technologies, the feasibility of their implementation to improve the level of informational and methodical competence of students of higher educational institutions was justified. It is found that the informational and methodological competence of future teachers is formed in the informational and educational environment using the information and communication technologies, as well as in continuous self-education.